The Influence Of Using Sea Sand As Aggregate On The Compressive Strength Of Concrete - Zebua, Dermawan; Harita, Hamedoni; Daeli, Serta Denius; Zalukhu, Muhammad Haris; Laia, Bimawijaya (Innovative Research in Civil and Environmental Engineering, 2024)
This study investigates the effect of using sea sand as fine aggregate on the compressive strength of concrete. The experimental research involved preparing concrete samples with varying proportions of sea sand, comparing their performance against conventional river sand. Compressive strength tests were conducted on the samples at 14 days, revealing that samples containing river sand exhibited significantly higher compressive strength than those with sea sand. The average compressive strength for concrete with 100% river sand was found to be 18.23 N/mm², while the presence of chlorides in sea sand, despite washing, adversely affected the strength. Statistical analysis confirmed a significant difference in strength between the control and sea sand mixtures. While sea sand presents an environmentally sustainable alternative, particularly in coastal regions, its use requires careful consideration of chloride content to prevent corrosion of steel reinforcement. This study concludes that sea sand can be a viable option for non-load-bearing or temporary structures, provided that appropriate measures are taken to mitigate potential risks.